Tallaqi Learning Model at Madrasah Tsanawiyah Tahfidz Quran - Nida Munfa'ati; Suyatno Suyatno; Sukirman Sukirman (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
The Quran memorization program in formal educational institutions such as schools and madrasas is something new that is very unique and attracts the attention of the public. This is due to the general school label, which focuses on pure science fields, even though there are religious lessons in it, maybe only two to four hours a week. This study aims to describe the Tallaqi learning model at the Al Barokah Purwantoro Qur'an memorization Madrasah. This study uses a qualitative method with a case study approach where data and research involve the principal, vice principal for curriculum, person in charge of the Quran memorization program, Quran memorization teachers and students, which are collected through observation and interviews, the collected data are analyzed using thematic analysis. The results of the study showed that the Tallaqi learning model at Madrasah Tsanawiyah Tahfidzul Quran Al Barokah was used in the learning process with teacher arrangements, student arrangements, time and place of study arrangements and the design of Quran memorization learning using the Tallaqi method